El Excentrico, 1963-09-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 20, 1963 [20 de septiembre de 1963]. Ano 13, No 23. Cover has advertisement for the Club Elite Semi-Formal Ball and Beauty Paegent and a picture of the Candelario Veliz Election Campaign.